Perjury in Early Tudor England - Cavill, Paul R. (Studies in church history, 2020)
The break with Rome was enforced through a nationwide programme of oath-taking. The Henrician regime resorted to oaths because they were already fundamental to the functioning of the polity. In the preceding half-century, activities as diverse as heresy prosecution, tax assessment and debt litigation depended upon oaths. Irrespective of their often mundane subject matter, oaths were held to be religious acts. Prolific oath-taking, however, led to frequent oath-breaking. Perjury was therefore a more pressing and broader concept than it is today. It was an offence against God, against oneself and against others. How this crime was prosecuted and punished sheds light on the intersection of religious doctrine, legal systems and social practice in pre-Reformation England. An analysis of perjury also draws attention to a jurisdictional shift that was underway before the Reformation. In 1485, church courts had exercised an extensive cognizance of perjury; by 1535, they no longer did. The most important factor contributing to this decline in ecclesiastical jurisdiction was the constraint imposed by common lawyers on what cases the church courts could hear. Common law defined the crime of perjury more narrowly than did canon law. Hence the contraction of the church's jurisdiction would alter how perjury was perceived.